Analysis of prognostic factors for borderline resectable pancreatic cancer after neoadjuvant chemotherapy: the importance of CA19-9 decrease in patients with elevated pre-chemotherapy CA19-9 levels. Issue 1 (January 2023) - Ono, Yoshihiro; Inoue, Yosuke; Ito, Hiromichi; Sasaki, Takashi; Takeda, Tsuyoshi; Ozaka, Masato; Sasahira, Naoki; Hiratsuka, Makiko; Matsueda, Kiyoshi; Oba, Atsushi; Sato, Takafumi; Saiura, Akio; et al.
Abstract: Background: Neoadjuvant chemotherapy (NAC) is widely used to treat borderline resectable pancreatic cancer. This study aimed to evaluate the serum carbohydrate antigen (CA)19-9 response, in association with survival, after four cycles of NAC-gemcitabine plus nab-paclitaxel. Methods: From 2015 to 2018, patients with borderline resectable pancreatic cancer were treated with NAC. Patients were stratified into two groups after excluding CA19-9 non-secretor: Group L (CA19-9 ≥2 and ≤500 U/mL) and Group H (CA19-9 >500 U/mL). The CA19-9 decrease during NAC was evaluated as a response of NAC and was assessed in association with survival concomitant with other prognosis factors. Results: Eighty-seven patients were evaluated (Group L: n = 43, Group H: n = 44). In intention-to-treat-based analysis, Group L exhibited significantly better progression-free survival (PFS) than Group H (median PFS: 24 vs 14months). In resection cohort, no correlation was detected between the CA19-9 decrease and survival in Group L. In Group H, the CA19-9 decrease ≤80% was associated with unfavorable survival in multivariate analysis [Hazard ratio: 4.738 ( P = 0.007)]. Conclusion: In patients with pre-treatment CA19-9 >500 U/mL, the CA19-9 decrease ≤80% was strongly associated with poor survival and new strategy should be reconsidered for these patients.